The Effect of Service Quality on Patient Satisfaction and Loyalty in Malaysia Muslim Friendly Hospital - Azman, N. A.I.; Rashid, N.; Ismail, N.; Shami, Samer (Opción, 2019)
Service quality is a must for Muslim friendly hospital to succeed and still main- tain the support of its participants. Muslim patients are realized that Islamic medical care is critical for their perceived health and satisfaction. Although this problem is emerging, the standard of medical care among patients is still less encouraging in the Malaysian Muslim friendly hospital. The objective of this study is to measure the relation among service quality and patient loyalty in the Muslim-friendly healthcare sector in the developing country of Malay- sia. An empirical study is conducted to look at the study model. This research applied a SERVQUAL model developed by Parasuraman in 1985, to meas- ure service quality in Malaysian Islamic medical care particularly in Muslim friendly hospital. The respondents were selected from inpatients and outpa- tients by adopting multi-stage cluster sampling. The hypotheses were tested using multiple regressions. There are four factors of service quality (tangible, empathy, reliability and responsiveness) have demonstrated strong links with loyalty. Therefore, the SERVQUAL model’s compliance aspect proved its val- ue by demonstrating the highest major factor in the overall model. It is hoped that the findings from the research are useful for the Islamic medical care policy makers by providing high-quality treatment, improving patient satis- faction, and ultimately promoting revisiting and recommending intentions to others.